Implementation of Teacher Professionalism in Digital Learning - Salsabilla Putri Andini; Aria Yudhantara Attariq; Fathan Syam Rimawan; Helmalia Fitri Atikah; Myisha Keilani Bukhari; Salsabilla Putri Andini (CV. Ulil Albab Corp, 2023)
This research will discuss how to apply teacher professionalism to learning in the digital era. In the current era of technological development, of course, it will also make it easier for all access to all types of information. Teachers professionalism needs to be improved so that teachers can carry out their implementation in a professional manner. The results of this study are expected to provide a new understanding regarding the relationship between the condition of teacher professionalism and digital learning. This research uses a literature study method with a qualitative approach. The data in this study were collected using the library research method. Data collection techniques in this study used various written sources such as articles, journals, and relevant documents related to research studies. This research focuses on studying teacher professionalism, digital learning, developing teacher professionalism and the urgency between teacher professionalism and digital learning. Then, the data that has been obtained in the literature study will be analyzed to find out how teacher professionalism is applied to digital era learning. The results of the study show that there is a relationship between teacher professionalism and digital era learning. Keywords: Teacher professionalism, learning, educator, digitalization